2000
DOI: 10.1152/ajpheart.2000.278.6.h1899
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for modulation of smooth muscle force by the p38 MAP kinase/HSP27 pathway

Abstract: Mitogen-activated protein (MAP) kinases signal to proteins that could modify smooth muscle contraction. Caldesmon is a substrate for extracellular signal-related kinases (ERK) and p38 MAP kinases in vitro and has been suggested to modulate actin-myosin interaction and contraction. Heat shock protein 27 (HSP27) is downstream of p38 MAP kinases presumably participating in the sustained phase of muscle contraction. We tested the role of caldesmon and HSP27 phosphorylation in the contractile response of vascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 29 publications
12
121
3
Order By: Relevance
“…noradrenaline were attenuated by p38 inhibition (Yamboliev et al, 2000;Ohanian et al, 2001;Meloche et al, 2000). However, there have been only a few reports of p38 inhibition on the vasoconstriction induced by both 5-HT and TXA2.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…noradrenaline were attenuated by p38 inhibition (Yamboliev et al, 2000;Ohanian et al, 2001;Meloche et al, 2000). However, there have been only a few reports of p38 inhibition on the vasoconstriction induced by both 5-HT and TXA2.…”
Section: Discussionmentioning
confidence: 96%
“…But there has been considerable evidence more recently to indicate that vasoconstrictive agonists activate multiple ancillary pathways that modulate the contractile response: protein kinase C (PKC) (Horowitz et al, 1996), Rho family G proteins (Somlyo and Somlyo, 2000), nonreceptor tyrosine kinases (Hughes and Wijetunge, 1998), and extracellular signal-regulated kinases (ERK1/2) (Ishihata et al, 2002) have been shown to play roles in smooth muscle contraction. Moreover, stress-activated protein kinases have also been implicated in sustained contraction through regulation of the phosphorylation of p38 mitogenactivated protein kinase (p38 MAPK) (Yamboliev et al, 2000). Activation of phospholipase C, Ca 2+ channels, tyrosine kinase and ERK MAPK have also been reported to be involved in 5-HTinduced contraction (Watts, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In many smooth muscles, p38 MAPK activation is linked to contraction (10,29,34,36,56), and in vascular tissues and gastrointestinal smooth muscle cells, Hsp27 phosphorylation is important for sustained contraction (32,40). Although in rat aorta smooth muscle cells, the inhibition of p38 MAPK and Hsp27 showed a significant reduction in contraction to ANG II but not NE (34).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have suggested that mitogen-activated protein (MAP) kinases may also impact on contractile responses in airways [64,[77][78][79] and other types of smooth muscle [80,81]. In particular, MLC20 are the proposed substrate of extracellular signal-regulated kinase (ERK)1 and 2 [82][83][84].…”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%